Writing Back Against Amazon’s Empire: Science Fiction, Corporate Storytelling, and the Dignity of the Workers’ Word - Max Haiven; Graeme Webb; Sarah Olutola; Xenia Benivolski (tripleC: Communication, Capitalism & Critique)
Since its founding in 1994 as an online bookstore, Amazon has “revolutionised” not only the market for literature but also expanded aggressively and transformatively in sectors including consumer retail, film and television, groceries, logistics, robotics, surveillance, AI, and web services. This growth and expansion is grounded in the firm’s internal and outward-facing rhetoric about its leading contribution to a brighter future, a narrative deeply inspired by the genre of science or speculative fiction (SF). But Amazon’s utopian vision is largely experienced as a dystopia by most of its rank-and-file workers, who labour under exploitative conditions of surveillance, robotization, and relentless managerial control. Hence our team inaugurated the Worker as Futurist project to support rank-and-file Amazon workers to read/watch SF stories to collectively understand their employer and its world, and also to write short, SF stories about “the world after Amazon.” In this preliminary report on the project, we explain the inspirations for the project and reflect on some of what we have learned from the participants, as well as some implications for the futures of platform workers generally.